Environmental profile of the electricity supplied in Portugal by the main suppliers - Ferreira, José (2016)
The main aim of this study was to assess and compare the environmental profile of 1 KWh of electricity supplied during 2014 by the four main electricity selling companies in Continental Portugal. The study was elaborated based on Life Cycle Assessment methodology and the method chosen for environmental impact assessment was EPD2013. The results show that the ENDESA´s electricity was the worst in terms of acidification, eutrophication, global warming, photochemical oxidation and ozone layer depletion while IBERDROLA´s electricity was the best for those impact categories and the worst in terms of abiotic depletion. Including in the study, the net electricity fed into the Portuguese and UCTE grid at the high voltage level, the conclusion is that the electricity at Portuguese grid presents the worst performance in terms of acidification, global warming and photochemical oxidation while the electricity at UCTE grid presents the worst performance in terms of eutrophication and ozone layer depletion.